Design and Simulation of Planar Inverted F Antenna (PIFA) for Long Term Evolution Systems - N. Taban, Iman; H. Khidhir, Ali; A. Naser, Ahmed (Al-Nahrain Journal of Science, 2022)
In this paper, a new calculator form is designed to calculate fundamental parameters for Planar Inverted F Antenna (PIFA). The special algorithm is configured by MATLAB R2015a software (version 8.5) in the form of a GUIDE programming language to estimate the value of antenna length (La) and width (Wa) by professional software Computer simulation technology (CST) microwave studio (Version 2019) is used to design and study the effects of each parameter in the antenna performance. The designed model was used directly in manufacturing through this method without any optimization or improvement. This antenna fabricated on the FR4 substrate has relative permittivity of 4.3 with a volume of (120´60´1.5) mm3 and the proposed antenna is fed by microstrip feeding structure. Simulation results of the (PIFA) show that the return loss, bandwidth, VSWR, and impedance are -52.100dB, 686 MHz, 1.0002 and 49.99 Ω respectively at resonant frequency 3.5 GHZ.